2019
DOI: 10.1101/778993
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Photoswitchable microtubule stabilisers optically control tubulin cytoskeleton structure and function

Abstract: Small molecule inhibitors provide a versatile method for studies in microtubule cytoskeleton research, since tubulin is not readily amenable to functional control using genetics. However, traditional chemical inhibitors do not allow spatiotemporally precise applications on the length and time scales appropriate for selectively modulating microtubule-dependent processes. We have synthesised a panel of taxane-based light-responsive microtubule stabilisers, whose tubulin hyperpolymerisation activity can be induce… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
(47 reference statements)
0
3
0
Order By: Relevance
“…Precision control of cytoskeleton-associated proteins with light has been recently demonstrated by using optogenetics involving proteins that indirectly act on the actin cyto­skeleton. On the one hand, engineering actin itself has been rather difficult due to the strong influence even small modifications have on its proper functioning. On the other hand, small-molecule photoswitches for the direct optical control of the microtubule cytoskeleton by tubulin polymerization inhibition have been developed , and have already led to applications in neuroscience, morphogenesis, and in vivo applications in embryology. Photoswitchable tubulin stabilizers were recently reported as well . By analogy, we expect that the small-molecule optojasps introduced here as photoswitchable F-actin modulators will provide a powerful tool for studying actin biology in a spatiotemporally controlled manner.…”
Section: Discussionmentioning
confidence: 85%
“…Precision control of cytoskeleton-associated proteins with light has been recently demonstrated by using optogenetics involving proteins that indirectly act on the actin cyto­skeleton. On the one hand, engineering actin itself has been rather difficult due to the strong influence even small modifications have on its proper functioning. On the other hand, small-molecule photoswitches for the direct optical control of the microtubule cytoskeleton by tubulin polymerization inhibition have been developed , and have already led to applications in neuroscience, morphogenesis, and in vivo applications in embryology. Photoswitchable tubulin stabilizers were recently reported as well . By analogy, we expect that the small-molecule optojasps introduced here as photoswitchable F-actin modulators will provide a powerful tool for studying actin biology in a spatiotemporally controlled manner.…”
Section: Discussionmentioning
confidence: 85%
“…Theaggregation behavior of microtubules (MTs) in our work has been demonstrated from the viewpoint of macrocycle-based host-guest complexation at the supramolecular level and subsequently,t he MT stabilizers based on azobenzene-modified paclitaxel (PTX) derivatives as photoswitchable small molecules have been investigated by Thorn-Seshold and co-workers in 2019. [2] In our case,t he microscopy results showed that the MT morphology was dramatically affected by the photoisomeric complexation between cyclodextrin (CD) and arylazopyrazole (AAP). No fibrous assembly as free MT could be observed in the presence of free PTX-CD,PTX-AAP,ortheir inclusion complex in the cis/trans states.T herefore,t he introduction of CD and AAP definitely influenced the selfassembling behavior between PTX and MT.M oreover, fluorescent-dye-staining assays demonstrated that the PTXderived host and guest compounds still possessed MT-targeting ability to some extent, because MT could be co-labeled by FITC-tagged antibodies and adamantane-containing RhB.…”
mentioning
confidence: 65%
“…We and others have reported on photoswitchable azobenzenebased inhibitors of tubulin polymerisation [10][11][12][13] that have since been used in studies of neuronal trafficking [14] and embryonic development [15,16], and we have recently reported biologically robust heterostilbenes that deliver green fluorescent protein (GFP)-orthogonal MT photocontrol [17]. However, in both azobenzene and heterostilbene scaffolds, the steric properties of the E-and Z-isomer are so different that the protein binding site shape determines that the Z-isomer (the lit-form) is the more bioactive one, without the possibility of sign inversion by substituent shifts.…”
Section: Introductionmentioning
confidence: 99%